1990
DOI: 10.1111/j.1469-8749.1990.tb08122.x
|View full text |Cite
|
Sign up to set email alerts
|

Power Spectral Analysis of the Eeg of Term Infants Following Birth Asphyxia

Abstract: SUMMARY The aim of this pilot study was to perform power spectral analysis of the EEGs of term infants following birth asphyxia, to establish its value as a prognostic indicator. 16 term infants were studied over an 18‐month period. Power spectral analysis was performed on the EEGs of babies with signs of hypoxic‐ishaemic encephalopathy at regular intervals during the first five days of life. It showed distinct changes following birth asphyxia, which were related to the eventual outcome of the babies. Absolute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1991
1991
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…It appears that abnormalities in the CFM pattern is of the greatest prognostic importance during the very first days of life. This is in agreement with the study of Bell et al who, in a pilot study of asphyxiated term infants, found no difference in absolute EEG spectral power between the poor and good outcome groups on the fifth day of life, but significant differences during the first three days of life (19).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It appears that abnormalities in the CFM pattern is of the greatest prognostic importance during the very first days of life. This is in agreement with the study of Bell et al who, in a pilot study of asphyxiated term infants, found no difference in absolute EEG spectral power between the poor and good outcome groups on the fifth day of life, but significant differences during the first three days of life (19).…”
Section: Discussionsupporting
confidence: 93%
“…Obviously, pharmacological treatment (i.e. sedatives and hypnotics) also influences the recorded CFM trace, but only to a limited degree, as was demonstrated for barbiturates (7,8,18,19).…”
Section: Discussionmentioning
confidence: 92%
“…However, the interpretation of prolonged EEG is time consuming and requires expertise, not present in every center. To fill this void, quantitative characterization of the EEG signal has been explored (Bell et al, 1990;Ahmed et al, 2016). In most results, spectral power is either used alone (Bell et al, 1990) or in combination with other features such as higher order statistics (Ahmed et al, 2016), in order to characterize the EEG of infants with HIE.…”
mentioning
confidence: 99%
“…To fill this void, quantitative characterization of the EEG signal has been explored (Bell et al, 1990;Ahmed et al, 2016). In most results, spectral power is either used alone (Bell et al, 1990) or in combination with other features such as higher order statistics (Ahmed et al, 2016), in order to characterize the EEG of infants with HIE. EEG spectral power can be expressed in absolute form (energy in a chosen frequency band) or in relative form (energy in a chosen frequency band divided by the total energy from all of the frequency bands).…”
mentioning
confidence: 99%
“…Moreover, abnormal tracings are related to neonatal death and in the survivors to impaired neurodevelopmental outcome [9][10][11][12][13] . One of the major problems in the care for high-risk neonates is to determine whether a baby's brain has suffered severe, irreversible damage [14] . The extent of the damage is important with respect to the reversibility of the compromised brain function.…”
Section: Introductionmentioning
confidence: 99%